2018
DOI: 10.1038/s42003-018-0151-2
|View full text |Cite
|
Sign up to set email alerts
|

Coordination between binocular field and spontaneous self-motion specifies the efficiency of planarians’ photo-response orientation behavior

Abstract: Eyes show remarkable diversity in morphology among creatures. However, little is known about how morphological traits of eyes affect behaviors. Here, we investigate the mechanisms responsible for the establishment of efficient photo-response orientation behavior using the planarian Dugesia japonica as a model. Our behavioral assays reveal the functional angle of the visual field and show that the binocular field formed by paired eyes in D. japonica has an impact on the accurate recognition of the direction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…When significance was found, the post hoc Dunnett’s test for multiple comparisons was performed. All chemotaxis assays were conducted at least three times and on at least two separate days in a dark room with only a red light of a wavelength that cannot be sensed by planarians ( 47 , 48 ).…”
Section: Methodsmentioning
confidence: 99%
“…When significance was found, the post hoc Dunnett’s test for multiple comparisons was performed. All chemotaxis assays were conducted at least three times and on at least two separate days in a dark room with only a red light of a wavelength that cannot be sensed by planarians ( 47 , 48 ).…”
Section: Methodsmentioning
confidence: 99%
“…An eye is composed of only two cell types: pigment cells are arranged into a semicircular eyecup, and photoreceptive visual neurons are located outside the eyecup, and therefore their eyes look like the convergent strabismus of higher animals’ eye structures. Since the planarian's two eyes compare light signals between the left and right eyes, the illumination should be applied horizontally (Akiyama et al., 2018). Since the light is attenuated according to the inverse square of distance, the distance between the light source and the assay chamber drastically affects the intensity of light illumination of the planarian, and therefore it should be carefully measured and set. Analysis of one individual in one assay chamber is recommended to avoid the influence of interaction among planarians, except when analyzing social behaviors. When transferring a planarian using a transfer plastic pipette, do not allow a planarian to adhere to the inside of the transfer plastic pipette.…”
Section: Tipsmentioning
confidence: 99%
“…An eye is composed of only two cell types: pigment cells are arranged into a semicircular eyecup, and photoreceptive visual neurons are located outside the eyecup, and therefore their eyes look like the convergent strabismus of higher animals' eye structures. Since the planarian's two eyes compare light signals between the left and right eyes, the illumination should be applied horizontally (Akiyama et al, 2018).…”
Section: Previous Versions Of Fiji R and Rstudio Compatible With Older Ormentioning
confidence: 99%
“…Recent molecular studies have demonstrated that, despite their simple body pattern, planarians have a sophisticated brain [18, 19]. Furthermore, studies using behavioral assays quantifying complex behaviors demonstrated that planarians display multiple environment-responsive behaviors mediated by the sensing of environmental signals, such as light, soluble chemicals, and temperature, via distinct sensory organs and integrating them in the brain [20–24]. Among their environment-responsive behaviors, planarians’ feeding is a complex behavior that can be divided into distinct processes.…”
Section: Introductionmentioning
confidence: 99%
“…Planarians ingest food via the pharynx, which is protruded out from the middle portion of the body, after localization of the target food using soluble substances released from foods as the clue [25, 26]. Despite the variety of available quantitative behavioral assays [20–24], a method to quantify the food intake as the endpoint of the feeding behavior is still lacking. Recently, the usefulness of the visualization of colored chalks ingested together with food and double-stranded RNA for achieving stable RNAi gene knockdown in planarians was described [27], which suggests that feeding of colored chalks plus food may help to quantify the amount of food ingested.…”
Section: Introductionmentioning
confidence: 99%